Umzug von Jungsozialisten mit Sturmfahnen, in eher ländlichem Gebiet (keine nähere Bestimmung möglich)
politischer Rahmen;politisches Leben (allgemein);politische Bewegung;Jugendbewegung politischer Rahmen;politisches Leben (allgemein);politische Ideologie;Sozialismus politischer Rahmen;politisches Leben (allgemein);politisches Leben (speziell);Demonstration